Method for adjusting results of pharmacoeconomic studies from country to country using Bayesian statistics - Janković Slobodan M.; Kostić Marina J.; Milovanović Jasmina R. (Srpsko lekarsko drustvo, 2021)
Introduction: Key problems when transferring results of pharmacoeconomic studies between countries are: relative infrequency of observational design, utilization of unreliable estimates of input parameters in many of modelling studies, not reporting variability of the study outputs (e.g. ICER, net monetary benefit) in a publication, and large differences in costs of healthcare services and drugs from country to country. Aim: The aim of this study was to estimate Incremental Cost-effectiveness Ratio (ICER) of denosumab vs. alendronate for treatment of osteoporosis in postmenopausal women in Serbia, using results of published pharmacoeconomic studies in United States of America (USA) and Japan. Material and Methods: The estimate of the ICER was made through the following steps: (1) scaling the ICER of the published studies to Serbian healthcare milieu using unit costs in Serbia, USA and Japan; (2) defining prior distribution of the ICER using adjusted results of the earlier published study; (3) defining sampling distribution of the ICER using adjusted results of the next published study; (4) estimating posterior distribution of the ICER and calculating the most probable values the ICER with Bayesian statistics. Results: The ICER of the prior distribution was 572,787.00 RSD, with 99% confidence interval from 1,116.00 to 998,051.00 RSD, and that of the sampling distribution 706,057.00 RSD, with 99% confidence interval from 1,122.00 to 999,308.00 RSD. The most probable ICER value from the posterior distribution was 752,912.00 RSD, with 99% confidence interval from 667,631.00 to 771,552.07 RSD. The estimated ICER was below one Gross Domestic Product (GDP) of Serbia per capita (the 2019 value: 780,063.60 RSD). Conclusions: Denosumab should be considered cost-effective in Serbia if one to three GDPs/capita/Quality Adjusted Life Year (QALY) gained is taken as the upper limit of willingness to pay by Serbian Health Insurance Fund.